(3TQM hbGjI GdQhGjI aj eSGFd GdgOGjIs - (3YHO GddWja Hf YHO GdYRjR Hf Cejf GdOjf Hf aQTJG GdcQeGfj, GdeYQha HGHf edc , (B801 (3g`s ((3MSjf Hf EOQjS Hf Ydjs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj LYd GdYde CQHM GdeJGLQ hGdecGSH hCQLM GdeaGNQ hGdeZGdH hfhQ HCfhGQg GdeTGQb hGdeZGQHs
(3BNQgG (B:s
(3hafO Hbhdg (B: (3hGdCbd WGgQI dCf GdeNJdW dh cGf GfGFjf jQjbgeG hjJjee GJaGbG hdh cGf CbdgeG fLSG jJMQi GJaGbG hjQjb eG ZdHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 59s
(3eYLe GdeDdajf (B2 / 215s
(3cTa GdXfhf (B2 / 2021s
(3TPQGJ GdPgH (B2 / 342s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs